Effect of Biotogrow Dosage on Black and White Sesame Varieties Quality - Dewi Ratna Nurhayati (Journal of Social Science, 2023)
Sesame as an industrial plant commodity product has functional properties and has good benefits for health and is needed for various industries, foodstuffs, and edible oil producers, as well as raw materials for industries: pharmaceuticals, margarine, soap, cosmetics , pesticides etc., because it contains > 40% unsaturated fat, minerals, protein, antioxidants (sesamin, and sesamolin). This research will provide solutions to cropping patterns and improve the welfare of the local community. This cultivation technique is able to optimize the planting medium to improve soil properties physically, chemically, biologically, can hold water and provide nutrients, which then makes it a source of plant needs in a sustainable manner. Research using Complete Randomized Block Design. Location of Trucuk Klaten. Treatment Factors Kinds of Sesame Varieties. The varieties are as follows, M1 = black sesame variety, M2 = white sesame variety, Biotogrow: D0 : without biotogrow 0 ml/l (as control), D1 : with a biotogrow dose of 1.5 ml/l, D2 : with a biotogrow dose of 2 ml/lD3 : with a biotogrow dose of 3 ml/l. Observation parameters included agronomic observations (flowering time, number of pods, weight of 1000 seeds, wet and dry stover) growing media conditions, agronomy and sesame growth. The data obtained were investigated for variance and continued with BNT 5%. As the fat content of white sesame is higher than black sesame which is 37% and 35.50%.